Authentic Assessment for Deep Learning in Early Childhood Education: Evidence from PAUD Institutions in North Sulawesi - Ni Dewi Eka Suwaryaningrat; Cindi Puspitasari; Triyana Triyana (Journal of Childhood Development, 2026)
Authentic assessment has become a crucial component of early childhood education as it provides comprehensive information regarding children's developmental achievements. However, the implementation of authentic assessment in many Indonesian Early Childhood Education (ECE) institutions remains challenging due to teachers' limited assessment competence, administrative workload, and insufficient digital support systems. This study aimed to analyze the implementation of authentic assessment practices in Early Childhood Education institutions in Tomohon and Manado, North Sulawesi, Indonesia. A qualitative multiple-case study approach was employed involving 24 ECE teachers, eight principals, and sixteen parents from eight PAUD institutions. Data were collected through classroom observations, semi-structured interviews, focus group discussions, and document analysis of assessment records. The data were analyzed using Braun and Clarke's (2021) reflexive thematic analysis, followed by cross-case analysis to identify recurring themes and contextual variations across participating institutions. The findings revealed that teachers primarily utilized observation checklists, anecdotal records, portfolios, and children's work documentation to assess developmental progress. Authentic assessment was found to support comprehensive monitoring of children's cognitive, language, social-emotional, motor, moral, and artistic development. Nevertheless, challenges included time constraints, lack of standardized assessment instruments, and limited digital literacy among educators. The study highlights the importance of continuous professional development and digital-based assessment systems to improve assessment quality. These findings contribute to strengthening authentic assessment practices in Indonesian ECE settings and support the implementation of child-centered learning within the Merdeka Curriculum framework.